Energy cost of front-crawl swimming at supra-maximal speeds and underwater torque in young swimmers - Zamparo, P.; Capelli, C.; Cautero, M.; Di Nino, A. (European Journal of Applied Physiology, 2000)
The energy cost of front-crawl swimming (Cs, kJ · m-1) at maximal voluntary speeds over distances of 50, 100, 200 and 400 m, and the underwater torque (T') were assessed in nine young swimmers (three males and six females; 12-17 years old). Cs was calculated from the ratio of the total metabolic energy (Es, kJ) spent to the distance covered. Es was estimated as the sum of the energy derived from alactic (AnAl), lactic (AnL) and aerobic (Aer) processes. In turn, AnL was obtained from the net increase of lactate concentration after exercise, AnAl was assumed to amount to 0.393 kJ · kg-1 of body mass, and Aer was estimated from the maximal aerobic power of the subject. Maximal oxygen consumption was calculated by means of the back-extrapolation technique from the oxygen consumption kinetics recorded during recovery after a 400-m maximal trial. Underwater torque (T', N · m), defined as the product of the force with which the feet of a subject lying horizontally in water tends to sink times the distance from the feet to the center of volume of the lungs, was determined by means of an underwater balance. Cs (kJ · m-1) turned out to be a continuous function of the speed (v, m · s-1) in both males (Cs=0.603 · 100.228v, r2=0.991; n=12) and females (Cs=0.360 · 100.339v, r2=0.919; n=24). A significant relationship was found between T' and Cs at 1.2 m · s-1; Cs=0.042T' + 0.594, r=0.839, n=10, P < 0.05. On the contrary, no significant relationships were found between Cs and T' at faster speeds (1.4 and 1.6 m · s-1). This suggests that T' is a determinant of Cs only at speeds comparable to that maintained by the subjects over the longest, 400-m distance [mean (SD) 1.20 (0.07) m · s-1].